What Determines Real Exchange Rates? The Nordic Countries - Anders Bergvall (Uppsala University, Department of Economics, 2002)
This paper presents a model yielding testable implications concerning the long-run co-movements of real exchange rates, relative productivity, the trade balance and terms of trade. Countries with higher productivity, trade deficits or improved terms of trade are found to have more appreciated real exchange rates, with the main channel of transmission working through the relative price of nontraded goods. Exogenous terms of trade shocks are found to be the most important determinant of long run movements in the real exchange rate for Denmark and Norway, while demand shocks account for most of the long run variance in the real exchange rate for Finland and Sweden.
urn:nbn:se:uu:diva-4445
Keywords: F31; F32; F41; 330; Real exchange rates; cointegration; variance decomposition; Kaufkraftparität; Handel; Kointegration; Dänemark; Norwegen; Schweden; Finnland